2019
DOI: 10.1111/1468-0009.12373
|View full text |Cite
|
Sign up to set email alerts
|

Service Delivery Models to Maximize Quality of Life for Older People at the End of Life: A Rapid Review

Abstract: We identified two overarching classifications of integrated geriatric and palliative care to maximize older people's quality of life at the end of life. Both are oriented to person‐centered care, but with differing emphasis on either function or symptoms and concerns. Policymakers should both improve access to palliative care beyond just the last months of life and increase geriatric care provision to maintain and optimize function. This would ensure that continuity and coordination for potentially complex car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 129 publications
1
68
0
1
Order By: Relevance
“…Although person-centred care sits at the heart of both geriatrics and palliative care specialties, these specialties also have different emphasis on function and/or symptoms and concerns. 14 How these different emphases play out when they converge in the context of medication and prescribing is a matter of critical concern for the safety and well-being of older people living in residential facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Although person-centred care sits at the heart of both geriatrics and palliative care specialties, these specialties also have different emphasis on function and/or symptoms and concerns. 14 How these different emphases play out when they converge in the context of medication and prescribing is a matter of critical concern for the safety and well-being of older people living in residential facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there is some movement to foster Geriatric Palliative Care as an inter-specialty (Voumard et al, 2018), it is notable that existing literature discusses how one form of speciality can be integrated into another, such as embedding palliative care into geriatric surgery or geriatric assessment (Gosney, 2007;Procter, 2012). A similar pattern was identified in a recent global review about maximising the quality of life or older people at the end of life noting two service models have been developed: Integrated Geriatric Care, emphasizing physical function, and Integrated Palliative Care, focusing mainly on symptoms and concerns (Evans et al, 2019). Studies on integrated care, however, have revealed how stakeholders have different understandings of what integration looks like and how it should operate, which can raise questions about its effectiveness (Bone et al, 2014) and that there is also a lack of clarity in the empirical literature that describes what the integration is in practice (Borgstrom & Barclay, 2015).…”
Section: Problems With Defining Specialismsmentioning
confidence: 89%
“…Healthcare delivery must be transformed to address the challenges of promoting shared decision-making with older adults with complex care needs [7,8]. This entails a shift from disease-specific to patient-centred models of care [9].…”
Section: Introductionmentioning
confidence: 99%